Development of handout teaching materials with a contextual approach to improve students' mathematical understanding - Ifat Sarifayani; Arif Abdul Haqq (Ilmu Inovasi Nusantara, 2022)
This study aims to determine which handout teaching materials with a contextual approach are suitable for use in learning mathematics, and to find out that handout teaching materials with a contextual approach are able to improve students' mathematical understanding. The type of research used is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collected in the form of observation sheets, interviews, questionnaires, and tests of students' mathematical understanding. The handout validation was validated by experts, namely material, language, and media experts, covering aspects of content, presentation, language, and graphics. In the validation results, material experts get a score of 3.44 which states